Evaluation of Potential Attractants for Six Species of Stored-Product Psocids (Psocoptera: Liposcelididae, Trogiidae). Issue 3 (22nd March 2015) - Diaz-Montano, John; Campbell, James F.; Phillips, Thomas W.; Throne, James E.
Abstract : Psocids have emerged as worldwide pests of stored commodities during the past two decades, and are difficult to control with conventional management tactics such as chemical insecticides. Therefore, it is necessary to investigate alternative management strategies, such as the use of attractants for monitoring and controlling psocids, which can be incorporated into integrated pest management programs for psocids. Using a two-choice pitfall test, we studied the response of adults of different ages and sexes of Liposcelis entomophila (Enderlein) (Psocoptera: Liposcelididae), Liposcelis paeta Pearman, Liposcelis decolor (Pearman), Liposcelis brunnea Motschulsky, Liposcelis corrodens (Heymons), and Lepinotus reticulatus Enderlein (Psocoptera: Trogiidae) to volatiles from different potential attractants including grains, grain-based oils, brewer's yeast, wheat germ, and commercially available kairomone lures. For all species tested, sex and age did not have a major influence on response to the different potential attractants. Brewer's yeast most consistently elicited the strongest response for psocids, but this response frequently was not different from that to wheat germ and wheat germ oil. The percentage response to brewer's yeast varied among the psocid species tested: L. decolor (73–78%), L. entomophila (62–73%), L. brunnea (64–68%), L. paeta (42–57%), Lep. reticulatus (40%), and L. corrodens (15–19%). Two psocids species ( L. corrodens and Lep. reticulatus ) had low responses to all the potential attractants evaluated compared with the other four species. These results show there is high potential for using these attractants in a psocid-monitoring program.